COMPUTATIONAL MODEL OF KAZAKH VOWEL–CONSONANT HARMONY (Journal of Problems in Computer Science and Information Technologies, 2026)
This study presents a computational model of morphological generation based on the agglutinative nature of the Kazakh language and vowel–consonant harmony. In this work, we model the Kazakh vowel–consonant harmony system, which governs allomorphic selection of suffixes based on both vowel and consonant properties. Using a rule based approach, the model generates verb and noun forms across various grammatical categories (tense, aspect, case, possession). Experimental results demonstrate the model’s high efficiency and full compliance of the generated word forms with vowel harmony rules. Specifically, thousands of combinations were created for derivative words (DTL), possession (POSS1, POSS2), and case (CASE) categories. This research makes a significant contribution to the development of natural language processing (NLP) morphological analysis and automatic translation systems for the Kazakh language.